Silicon-carbon composite material, preparation method and application thereof, and battery
By forming metal plating, silicon alloy particles and amorphous silicon particles on the porous carbon matrix and covering the outer layer with carbon layers, silicon carbon composite materials with high conductivity and structural stability were prepared, which solved the problem of unstable structure and rapid attenuation of silicon-based negative electrode materials, and achieved efficient battery performance.
Patent Information
- Application Number
- CN202411764614.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicon-based negative electrode material has an unstable structure, and the volume expands after being embedded in lithium, causing powder rupture during the cycle, resulting in rapid attenuation of battery capacity.
A porous carbon matrix is used as the matrix, and a metal plating layer is formed on the pore wall through vapor deposition reaction. Then silicon alloy particles are prepared on the surface of the plating layer, and epitaxially grown along the silicon alloy particles through amorphous silicon particles, and finally a carbon cladding layer is formed on the outer layer to form a silicon-carbon composite material with excellent conductivity and structural stability.
It achieves high-quality specific capacity and excellent high- and low-temperature cycle stability, extends the service life of the battery and reduces the preparation cost.
Smart Images

Figure CN119517968A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite material and a preparation method, application and battery thereof. Background Art
[0002] With the advent of the digital and intelligent era, various electronic devices such as mobile phones, computers, power tools, and electric vehicles are increasingly used in life, so the demand for energy is increasing day by day, prompting researchers to further develop green energy represented by solar energy, wind energy, tidal energy, etc. However, they are all intermittent energy sources and need to be used in conjunction with energy storage devices. Lithium-ion batteries are widely used in consumer electronics, power storage, and large power grids due to their high energy density, high power density, high output voltage, and no memory effect.
[0003] Lithium-ion batteries are mainly composed of positive electrode, negative electrode, electrolyte, and separator. The positive and negative electrodes are active components and are carriers of energy storage. As for the negative electrode, graphite materials are widely used at present, and their capacity is close to the theoretical specific capacity (372 mAh g -1 ), so it is necessary to develop negative electrode materials with higher specific capacity. Silicon negative electrode has a high theoretical specific capacity (4200 mAh g -1 ) and a low electrochemical lithium insertion potential (<0.1 V vs. Li / Li + ), is an ideal negative electrode material for the next generation of lithium-ion batteries. However, after lithium is inserted into the silicon negative electrode, a large volume expansion (>300%) will occur, and powdering and cracking will occur during the cycle, which will continuously consume the electrolyte to form a thick solid electrolyte membrane (SEI membrane), causing the battery capacity to decay rapidly. On the other hand, the conductivity of the silicon material itself is not high (about 10 -3 S cm -1 ), which is not conducive to the rapid transmission of electrons and ions, and the capacity of active materials is difficult to fully utilize at high current density.
[0004] Patent application CN 115020689 A introduces a nano silicon-carbon composite material for secondary lithium batteries, its preparation method and application. The nano silicon-carbon composite material includes: a porous carbon matrix, a coating containing transition metal elements and nano silicon particles; the coating covers the pore walls of the through-holes and the outer surface of the porous carbon microspheres, and the nano silicon particles are deposited in the through-holes and on the outer surface of the porous carbon microspheres. The coating is physically isolated from the porous carbon matrix to prevent the nano silicon particles from reacting with the porous carbon matrix to form silicon carbide during the deposition process, thereby reducing the generation of irreversible capacity and improving the first cycle efficiency of the battery. However, in the preparation process, since the liquid phase method is used for chemical plating, it is impossible to ensure that most of the voids inside the porous carbon are plated. Therefore, the carbon matrix used is required to have a special void structure (such as through-holes) to facilitate liquid penetration reaction plating. The higher requirements for raw materials are not only not conducive to the stability of the silicon-carbon composite material during use, but also increase the preparation cost of the silicon-carbon composite material. Summary of the invention
[0005] The present invention solves the problems of unstable structure and rapid capacity decay of silicon-based negative electrode materials in the prior art, and proposes a silicon-carbon composite material and its preparation method, application and battery. The silicon-carbon composite material of the present invention has excellent electrical conductivity and structural stability, and a battery using the silicon-carbon composite material can achieve high mass specific capacity and excellent high and low temperature cycle stability.
[0006] The present invention adopts the following technical solutions to solve the above technical problems:
[0007] The present invention provides a silicon-carbon composite material, comprising:
[0008] Porous carbon matrix;
[0009] A metal coating, wherein the metal coating is located on the pore walls of the porous carbon matrix;
[0010] Silicon alloy particles, wherein the silicon alloy particles are located on the surface of the metal coating;
[0011] Amorphous silicon particles, the amorphous silicon particles epitaxially growing along the silicon alloy particles; and
[0012] A carbon coating layer is located on the outer layer.
[0013] In the present invention, the silicon-carbon composite material has a D 10 The thickness may be 2-6 μm, for example, 4.59 μm, 4.76 μm, 4.84 μm, 4.96 μm, 5.04 μm, 5.10 μm, 5.19 μm, 5.44 μm or 5.46 μm.
[0014] In the present invention, the silicon-carbon composite material has a D 50 The thickness may be 6-11 μm, for example, 6.78 μm, 7.10 μm, 7.14 μm, 7.17 μm, 7.21 μm, 7.23 μm, 7.26 μm, 7.37 μm, 7.53 μm or 7.65 μm.
[0015] In the present invention, the silicon-carbon composite material has a D 90 The thickness may be 11-30 μm, for example, 13.93 μm, 14.11 μm, 14.25 μm, 14.41 μm, 14.46 μm, 14.54 μm, 14.55 μm, 14.73 μm or 14.85 μm.
[0016] In the present invention, the particle size distribution span of the silicon-carbon composite material is ( ) may be 1.05-1.75, for example, 1.15, 1.19, 1.24, 1.26, 1.31, 1.33, 1.34, 1.35, 1.36 or 1.44.
[0017] In the present invention, the silicon loading of the silicon-carbon composite material may be 30%-70%, for example, 37.35%, 41.76%, 41.82%, 42.64%, 42.94%, 43.17%, 43.46%, 43.60%, 44.10% or 44.23%; the percentage is the percentage of the mass of silicon in the silicon-carbon composite material to the total mass of the silicon-carbon composite material. Here, the "silicon element" includes silicon elements in silicon alloy particles and silicon elements in amorphous silicon particles.
[0018] In the present invention, the BET specific surface area of the silicon-carbon composite material can be 2-7 m 2 / g, for example, 2.96 m 2 / g, 3.04 m 2 / g, 3.16 m 2 / g, 3.51 m 2 / g, 3.63 m 2 / g, 4.98 m 2 / g, 5.42 m 2 / g, 5.63 m 2 / g, 5.71 m 2 / g or 6.01 m 2 / g.
[0019] In the present invention, the true density of the silicon-carbon composite material can be 1.71-2.21 g / cm 3 , for example, 1.82 g / cm 3 , 1.84 g / cm 3 , 1.87 g / cm3 , 1.88 g / cm 3 , 1.90 g / cm 3 , 1.91 g / cm 3 , 1.93 g / cm 3 or 1.94 g / cm 3 .
[0020] In the present invention, the tap density of the silicon-carbon composite material can be 0.50-0.77 g / cm 3 , for example 0.55 g / cm 3 , 0.58 g / cm 3 , 0.59 g / cm 3 , 0.60 g / cm 3 , 0.61 g / cm 3 , 0.63 g / cm 3 , 0.65 g / cm 3 , 0.66 g / cm 3 or 0.68 g / cm 3 .
[0021] In the present invention, the compacted density (3t) of the silicon-carbon composite material may be 0.975-1.075 g / cm 3 , for example, 0.991 g / cm 3 , 0.992 g / cm 3 , 0.996 g / cm 3 , 0.998 g / cm 3 , 1.004 g / cm 3 , 1.006 g / cm 3 , 1.010g / cm 3 , 1.011 g / cm 3 , 1.016 g / cm 3 or 1.039 g / cm 3 The compaction density (3t) means: the compaction density of the silicon-carbon composite material is measured under a pressure of 3t.
[0022] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0023] S1, subjecting a porous carbon substrate to a first vapor deposition reaction using a first deposition gas to form a metal coating on the pore walls of the porous carbon substrate to obtain a first precursor; wherein the first deposition gas includes a first metal source gas;
[0024] S2, subjecting the first precursor to a second vapor deposition reaction using a second deposition gas to form silicon alloy particles on the surface of the metal coating to obtain a second precursor; wherein the second deposition gas includes a second metal source gas and a second silicon source gas;
[0025] S3, subjecting the second precursor to a third vapor deposition reaction using a third deposition gas, epitaxially growing amorphous silicon particles on the silicon alloy particles, to obtain a third precursor; wherein the third deposition gas comprises a third silicon source gas;
[0026] S4, carbon-coating the third precursor to obtain a silicon-carbon composite material.
[0027] In the present invention, the raw material of the porous carbon matrix in step S1 can be one or more of asphalt-based, coal-based, resin-based and bio-based.
[0028] The porosity of the porous carbon matrix in step S1 may be 70-90%.
[0029] The pore volume of the porous carbon matrix in step S1 may be 0.55-2.2 m 3 / g.
[0030] The BET specific surface area of the porous carbon substrate in step S1 can be 800-2200 m 2 / g.
[0031] In the present invention, the first vapor deposition reaction in step S1 is preferably plasma enhanced chemical vapor deposition (PECVD), wherein the vapor deposition reaction is carried out in conventional equipment, for example, in a plasma enhanced chemical vapor deposition (PECVD) furnace.
[0032] In step S1, the total flow rate of the first deposition gas may be 400-800 sccm.
[0033] In step S1, the flow rate of the first metal source gas may be 2-42 sccm, for example, 10 sccm.
[0034] In the present invention, in step S1, the first metal source gas is a metal compound gas.
[0035] In the present invention, the metal compound gas is obtained by gasification (such as volatilization, evaporation or sublimation) of a metal compound, and the metal compound needs to have certain volatility and reaction stability. The metal compound gas has no mandatory requirements on the type of metal source, but most transition metal compound gases have the above characteristics. Generally, metal compounds of main group metal elements are relatively stable and not conducive to gas phase ionization.
[0036] In the present invention, the metal compound gas is preferably a transition metal compound gas.
[0037] In the present invention, the metal compound gas is preferably an organic metal compound gas.
[0038] In some specific embodiments, the first and second metal compound gases each independently include, but are not limited to, Ag compound gas, Cu compound gas, Al compound gas, Sn compound gas, Ge compound gas or W compound gas.
[0039] Preferably, the Ag compound gas includes one or more of silver bromide gas, silver methanesulfonate gas and silver trifluoromethanesulfonate gas.
[0040] Preferably, the Cu compound gas includes: copper chloride gas and / or copper acetylacetonate gas.
[0041] Preferably, the Al compound gas includes one or more of aluminum chloride gas, aluminum bromide gas and triethylaluminum gas.
[0042] Preferably, the Sn compound gas includes one or more of dibutyltin dichloride gas, tin tetrachloride gas and trimethyltin gas.
[0043] Preferably, the Ge compound gas includes one or more of germanium tetrafluoride gas, germanium tetraiodide gas and tetraethylgermanium gas.
[0044] Preferably, the W compound gas includes one or more of tungsten hexafluoride gas, tungsten hexachloride gas and tungsten hexacarbonyl gas.
[0045] Preferably, in step S1, the first deposition gas further comprises a carrier gas and / or a reduction reaction gas. Preferably, the flow rate of the carrier gas is 250-650 sccm, for example, 390 sccm. Preferably, the carrier gas is argon. Preferably, the flow rate of the reduction reaction gas is 20-200 sccm, for example, 100 sccm. Preferably, the reduction reaction gas is hydrogen.
[0046] In step S1, the deposition pressure of the first vapor deposition reaction may be 5-255 Pa, for example, 30 Pa.
[0047] In step S1, the radio frequency power of the first vapor deposition reaction may be 150-450 W, for example, 400 W.
[0048] In step S1, the deposition temperature of the first vapor deposition reaction may be 300-800°C, for example, 450°C.
[0049] In step S1, the deposition time of the first vapor deposition reaction may be 5-150 min, for example, 30 min.
[0050] In the present invention, the metal coating is mainly located on the pore walls of the porous carbon substrate rather than on the surface of the porous carbon substrate, which is mainly achieved by controlling the deposition amount through process.
[0051] If the metal coating is deposited on the surface of the porous carbon matrix, although it can improve the intrinsic conductivity of the material and reduce polarization, it will also affect the diffusion deposition of silane in the subsequent vapor deposition process, causing most of the silicon particles to be deposited on the surface of the porous carbon matrix rather than in the pores of the porous carbon matrix, causing the electrochemical performance of the material to deteriorate seriously. Therefore, it is necessary to avoid excessive deposition of the metal coating through process control.
[0052] In the present invention, preferably, in step S2, the total flow rate of the second deposition gas is 400-800 sccm.
[0053] Preferably, in step S2, the flow rate of the second silicon source gas is 10-100 sccm, for example, 25 sccm.
[0054] Preferably, in step S2, the second silicon source gas is one or more of silane and silane halide, wherein the silane is preferably monosilane and / or dimethylsilane.
[0055] In a preferred embodiment, in step S2, the second deposition gas further comprises a carrier gas, wherein the flow rate of the carrier gas is preferably 250-650 sccm, wherein preferably, the carrier gas is argon.
[0056] Preferably, in step S2, the flow rate of the second metal source gas is 10-100 sccm.
[0057] In step S2, the deposition pressure of the second vapor deposition reaction may be 5-255 Pa, for example, 10 sccm.
[0058] In step S2, the radio frequency power of the second vapor deposition reaction may be 150-450 W, for example, 400 W.
[0059] In step S2, the deposition temperature of the second vapor deposition reaction may be 300-800°C, for example, 450°C.
[0060] In step S2, the deposition time of the second vapor deposition reaction may be 5-150 min, for example, 30 min.
[0061] In the present invention, preferably, the total flow rate of the third deposition gas may be 400-800 sccm.
[0062] In a specific implementation, the second vapor deposition reaction in step S3 is carried out in a common chemical vapor deposition equipment in the industry, such as a fluidized bed, a rotary furnace, a fixed bed, and the like.
[0063] In a preferred embodiment, the third deposition gas in step S3 further comprises a carrier gas, wherein the flow rate of the carrier gas may be 275-675 sccm, wherein preferably, the carrier gas is nitrogen or argon.
[0064] The flow rate of the third silicon source gas in step S3 may be 30-300 sccm, for example, 150 sccm.
[0065] The third silicon source gas in step S3 may be one or more of monosilane, dimethylsilane and silane halide.
[0066] The deposition temperature of the third vapor deposition reaction in step S3 may be 300-800° C., for example, 530° C.
[0067] The deposition time of the third vapor deposition reaction in step S3 may be 30-360 min, for example, 160 min.
[0068] In a preferred embodiment, the carbon coating in step S4 is performed by a vapor deposition reaction using a fourth deposition gas, wherein the fourth deposition gas includes a carbon source gas.
[0069] In step S4, the flow rate of the carbon source gas may be 30-300 sccm, for example, 100 sccm. The carbon source gas may include one or more of methane, ethylene and acetylene.
[0070] The total flow rate of the fourth deposition gas in step S4 may be 400-800 sccm.
[0071] In a preferred embodiment, the fourth deposition gas in step S4 further comprises a dilution gas, wherein the flow rate of the dilution gas may be 275-675 sccm, for example, 400 sccm, wherein the dilution gas may be nitrogen or argon.
[0072] The carbon coating temperature in step S4 may be 400-800°C, for example 600°C.
[0073] The carbon coating time in step S4 may be 0.5-10 h, for example 224 min.
[0074] In the present invention, the coating prepared by the gas phase method has the characteristics of short preparation time and high coating uniformity, which is an advantage that the liquid phase method or the gel method does not have.
[0075] In the present invention, the preparation of the metal coating, the preparation of the metal-silicon alloy particles and the epitaxial growth of the amorphous silicon particles all adopt similar process routes, which is conducive to the continuity of the process.
[0076] The present invention provides a silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material.
[0077] The present invention provides an application of the silicon-carbon composite material as described above as an electrode material in a battery.
[0078] Wherein, the electrode material is preferably a negative electrode material.
[0079] The present invention also provides a pole piece, which comprises the above silicon-carbon composite material.
[0080] Wherein, the electrode sheet is preferably a negative electrode sheet.
[0081] The present invention also provides a battery, which comprises the above silicon-carbon composite material.
[0082] In the present invention, the battery is preferably a lithium ion battery.
[0083] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0084] The reagents and raw materials used in the present invention are commercially available.
[0085] The positive and progressive effects of the present invention are:
[0086] (1) The preparation method of the silicon-carbon composite material of the present invention deposits a metal coating on the pore wall of a porous carbon matrix through a vapor deposition reaction. Compared with the conventional gel method, the coating can be completed in the shortest time, which helps to shorten the production cycle; on the other hand, the prepared metal coating is more uniform, which helps to reduce polarization and improve the conductivity of the negative electrode material.
[0087] (2) In the preparation method of the silicon-carbon composite material of the present invention, the metal-silicon alloy particles prepared on the surface of the metal coating are used as deposition anchor points in the subsequent silicon deposition process, and amorphous silicon is deposited and grown along the epitaxy of the metal-silicon alloy particles. Therefore, the active material and the carbon matrix can form a closer connection, thereby improving the stability of the overall structure of the negative electrode material.
[0088] (3) The method for preparing the silicon-carbon composite material of the present invention has a unique three-dimensional structural design. The pore structure helps to alleviate the volume effect of the negative electrode material during the cycle, and the amorphous silicon particles are anchored on the surface of the metal coating on the porous carbon pore wall. This composite structure can enable the electrode material to achieve high mass specific capacity and excellent high and low temperature cycle stability at high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Figure 1 This is a flow chart of the preparation method of the silicon-carbon composite material obtained in Example 1 of the present invention.
[0090] Figure 2 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 1 of the present invention, wherein 1 is a metal coating, 2 is Ag-Si alloy particles, 3 is amorphous silicon particles, 4 is a porous carbon matrix, and 5 is a carbon coating layer.
[0091] Figure 3 This is the charge and discharge curve of the silicon-carbon composite material obtained in Example 1 of the present invention.
[0092] Figure 4 This is the rate performance result of the silicon-carbon composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0093] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0094] Porous carbon matrix: Jinan Shengquan Group Co., Ltd., ZLD-1.
[0095] Silver trifluoromethanesulfonate: Nanshi reagent, C0335519351.
[0096] Copper acetylacetonate: Thermo Fisher Scientific, A14920.
[0097] Triethylaluminum: MacLean's reagent, T819169.
[0098] Trimethyltin: Hubei Xinhongli Chemical Co., Ltd.
[0099] Tetraethylgermanium: MacLean's reagent, T867598.
[0100] Tungsten hexafluoride: Hubei Maotu Runda Gas Co., Ltd.
[0101] Example 1
[0102] S1. Take 30 g of commercially available porous carbon substrate (pore volume 0.725 cm 3 / g, BET specific surface area is 1720m 2 / g) was placed in a PECVD furnace, the deposition pressure was 30 Pa, the RF power was 400 W, the deposition temperature was 450 °C, argon was used as a carrier gas with a flow rate of 390 sccm, hydrogen was used as a reducing gas with a flow rate of 100 sccm, silver trifluoromethanesulfonate gas was introduced into the furnace body, the steam flow rate was 10 sccm, and the first precursor was obtained after the reaction for 30 min;
[0103] S2. After step S1 is completed, stop introducing hydrogen, increase the argon flow rate to 465 sccm, introduce monosilane gas into the furnace body at a flow rate of 25 sccm, and keep the deposition pressure, RF power, deposition temperature and silver trifluoromethanesulfonate vapor flow rate unchanged during the process, and obtain the second precursor after reacting for 20 minutes;
[0104] S3, transferring the material obtained in step S2 to a fluidized bed reactor, and performing silicon deposition reaction by chemical vapor deposition process, with the deposition temperature being 530° C., nitrogen being used as carrier gas, the nitrogen flow rate being 350 sccm, monosilane being used as silicon source gas, the flow rate of monosilane being 150 sccm, and reacting for 160 min to obtain a third precursor;
[0105] S4: After step S3 is completed, the furnace temperature is increased to 600°C, the nitrogen flow rate is 400 sccm, acetylene is used as the carbon source gas, the acetylene flow rate is 100 sccm, and the silicon-carbon composite material is obtained after reacting for 224 minutes. The preparation method flow chart and structural schematic diagram of the obtained silicon-carbon composite material are shown in Figure 1 and Figure 2 shown.
[0106] Example 2
[0107] The difference between this embodiment and embodiment 1 is that the radio frequency power applied in steps S1 and S2 is 370 W, and the other conditions are exactly the same as those in embodiment 1.
[0108] Example 3
[0109] The difference between this embodiment and embodiment 1 is that the radio frequency power applied in steps S1 and S2 is 430 W, and the other conditions are exactly the same as those in embodiment 1.
[0110] Example 4
[0111] The difference between this embodiment and embodiment 1 is that the metal compound gas used in steps S1 and S2 is copper acetylacetonate to obtain a copper-containing silicon-carbon composite material, and the other conditions are exactly the same as those in embodiment 1.
[0112] Example 5
[0113] The difference between this embodiment and embodiment 4 is that the deposition temperature applied in steps S1 and S2 is 400° C., and the other conditions are exactly the same as those in embodiment 4.
[0114] Example 6
[0115] The difference between this embodiment and embodiment 1 is that the metal compound gas used in steps S1 and S2 is adjusted to triethylaluminum gas to obtain an aluminum-silicon-carbon composite material, and the other conditions are exactly the same as those in embodiment 1.
[0116] Example 7
[0117] The difference between this embodiment and embodiment 6 is that the deposition temperature applied in steps S1 and S2 is 400° C., and the other conditions are exactly the same as those in embodiment 6.
[0118] Example 8
[0119] The difference between this embodiment and embodiment 1 is that the metal compound gas used in steps S1 and S2 is trimethyltin gas to prepare a tin-containing silicon-carbon composite material, and the other conditions are exactly the same as those in embodiment 1.
[0120] Example 9
[0121] The difference between this embodiment and embodiment 1 is that the metal compound gas used in steps S1 and S2 is tetraethylgermanium gas to obtain a germanium-containing silicon-carbon composite material, and the other conditions are exactly the same as those in embodiment 1.
[0122] Example 10
[0123] The difference between this embodiment and embodiment 1 is that the metal compound gas used in steps S1 and S2 is tungsten hexafluoride gas to obtain a tungsten-containing silicon-carbon composite material, and the other conditions are exactly the same as those in embodiment 1.
[0124] Comparative Example 1
[0125] The difference between this comparative example and Example 1 is that step S1 is not performed, that is, Ag-Si alloy particles are directly deposited on the pore walls of the porous carbon matrix to obtain a silver-containing silicon-carbon composite material without an Ag coating, and the other conditions are exactly the same as in Example 1.
[0126] Comparative Example 2
[0127] The difference between this comparative example and Example 4 is that step S1 is not performed, that is, Cu-Si alloy particles are directly deposited in the porous carbon voids to obtain a copper-containing silicon-carbon composite material without a Cu coating, and the other conditions are exactly the same as those in Example 4.
[0128] Comparative Example 3
[0129] The difference between this comparative example and Example 1 is that only steps S1 and S3-S4 are performed to obtain a silicon-carbon composite material that does not contain Ag-Si alloy particles, and the other conditions are exactly the same as those in Example 1.
[0130] Comparative Example 4
[0131] The difference between this comparative example and Example 1 is that step S4 is not performed, and a silicon-carbon composite material without a carbon coating layer is obtained, and the other conditions are exactly the same as those in Example 1.
[0132] Effect Example 1
[0133] Physical and chemical performance test:
[0134] Testing method for particle size of silicon-carbon composite materials: using a laser particle size analyzer (Malvern-2000) for testing.
[0135] Testing method for silicon content in silicon-carbon composite materials: using TGA thermogravimetric analyzer (TG209F3) for testing.
[0136] Testing method for specific surface area of silicon-carbon composite materials: using BET specific surface area tester for testing.
[0137] Testing method for true density of silicon-carbon composite materials: using a fully automatic density meter (AccuPycⅡ1340) for testing.
[0138] Testing method for compaction density of silicon-carbon composite materials: Use compaction density meter (LD43, PowerTest Instrument) to test and obtain compaction density under 3t pressure.
[0139] Testing method for tap density of silicon-carbon composite materials: Use tap density analyzer (Dandong Better BT-311) for testing.
[0140] The physical and chemical properties of the silicon-carbon composite materials obtained in Examples 1 to 10 and Comparative Examples 1 to 4 were tested by the above method, and the results are shown in Table 1.
[0141] Effect Example 2
[0142] Electrochemical performance test:
[0143] 1. Pole piece production and battery assembly:
[0144] The silicon-carbon composite material prepared in the embodiment of the present invention can be used as a negative electrode material for lithium-ion batteries. First, the prepared silicon-carbon composite material, conductive carbon black (SP), and LA132 binder are homogenized in a mass ratio of 7:1.5:1.5, and then evenly coated on a copper foil current collector (14×25cm, 9μm). The coated copper foil is dried at a constant temperature of 120°C for 720 min under vacuum conditions. The dried pole piece is rolled with a roller press, and finally the pole piece is cut into a round piece with a diameter of 12 mm by a punching machine, so as to obtain the electrode piece to be tested.
[0145] The counter electrode was made of metallic lithium foil and assembled into a CR2025 button cell in a glove box filled with argon.
[0146] 2. Electrochemical performance test:
[0147] The charge and discharge performance of the assembled button cells was tested using the Wuhan Blue Electric Battery Testing System (LAND), and the assembled button cells were left to stand for 12 h.
[0148] (1) First charge capacity and first coulombic efficiency (first efficiency)
[0149] The test method for charging capacity is: discharge at 0.05C constant current to 5mV, and then charge at 0.1C constant current to obtain the capacity as the charging capacity;
[0150] The test method for discharge capacity is: discharge at 0.05C constant current to 5mV, and then discharge at 0.01C to 1mV;
[0151] The first effect can be calculated by the following formula:
[0152] First effect = discharge capacity / charge capacity.
[0153] (2) Rate performance
[0154] The rate performance test method is: charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current for 5 cycles, recorded as 0.1C / 0.1C;
[0155] 0.1C / 0.1C, 1C / 0.1C, 2C / 0.1C, 3C / 0.1C are tested with the same steps.
[0156] The charge and discharge capacity, initial efficiency and rate performance of Examples 1-10 and Comparative Examples 1-4 were tested by the above test method, and the test results are shown in Table 2. Among them, the test results of the charge and discharge specific capacity of the silicon-carbon composite material obtained in Example 1 are shown in Figure 3 As shown, the rate performance of the silicon-carbon composite material obtained in Example 1 is as follows Figure 4 shown.
[0157] (3) Cycling performance at different temperatures
[0158] At temperatures of 0°C, 25°C or 45°C, the battery was charged to 2V at a constant current of 0.1C, and then discharged to 5mV at a constant current of 0.1C, which was counted as one cycle.
[0159] The rate performance and 100 cycle performance at different temperatures of Examples 1-10 and Comparative Examples 1-4 were tested by the above test method. The test results are shown in Table 3.
[0160] Table 1
[0161] project <![CDATA[D 10 (μm)]]> <![CDATA[D 50 (μm)]]> <![CDATA[D 90 (μm)]]> <![CDATA[(D 90 -D 10 ) / D 50 ]]> Silicon content (%) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[True density (g / cm 3 )]]> <![CDATA[Compaction density (g / cm 3 )]]> <![CDATA[Tap density (g / cm 3 )]]> Example 1 4.96 7.21 14.41 1.31 43.60% 3.04 1.91 1.039 0.66 Example 2 5.19 7.37 13.93 1.19 41.82% 3.16 1.88 0.991 0.65 Example 3 5.10 6.78 14.85 1.44 43.17% 5.42 1.94 1.011 0.68 Example 4 5.10 7.23 14.73 1.33 44.23% 5.71 1.90 1.006 0.63 Example 5 4.76 7.14 14.46 1.36 42.64% 6.01 1.87 0.998 0.60 Example 6 5.04 7.10 14.55 1.34 41.76% 4.98 1.82 0.996 0.55 Example 7 5.44 7.26 14.46 1.24 37.35% 5.63 1.84 1.016 0.58 Example 8 5.46 7.65 14.25 1.15 43.46% 3.51 1.90 0.992 0.61 Example 9 4.84 7.17 14.54 1.35 44.10% 3.63 1.88 1.010 0.59 Example 10 4.59 7.53 14.11 1.26 42.94% 2.96 1.93 1.004 0.68 Comparative Example 1 4.57 7.61 14.50 1.30 40.71% 3.11 1.97 1.008 0.64 Comparative Example 2 4.63 7.01 13.91 1.33 39.02% 3.54 1.99 1.006 0.62 Comparative Example 3 5.12 7.25 14.70 1.32 43.70% 4.14 1.86 1.031 0.63 Comparative Example 4 4.88 7.26 13.93 1.25 49.73% 147.61 1.95 1.022 0.61
[0162] The physical and chemical data of the silicon-carbon composite materials of Examples 1-10 and Comparative Examples 1-4 are shown in Table 1. All the prepared silicon-carbon composite materials have similar particle size characteristics, but show large differences in silicon content and specific surface area, which is the result of different types of metal compound gases and deposition processes.
[0163] It can be seen from Example 1 that when silver trifluoromethanesulfonate is used as the metal source, the obtained silicon-carbon composite material has a relatively high silicon content and true density, and a relatively lower specific surface area, indicating that silver is effectively loaded into the porous carbon matrix;
[0164] It can be seen from Examples 2-3 that when a higher RF power is used, the particle size distribution of the obtained silicon-carbon composite material becomes wider and the specific surface area is relatively higher, indicating that the deposition process at this time is not very stable and some particles may not be deposited inside the porous carbon.
[0165] The silicon-carbon composite materials obtained in Examples 4-7 have a relatively higher specific surface area and a relatively low true density, indicating that when copper acetylacetonate and triethylaluminum are used as metal sources, the plasma generated by the cracking has a relatively low free path and is deposited in the surface area before diffusing into the porous carbon.
[0166] Comparative Example 4 has the relatively highest specific surface area. This is because the sample was not subjected to carbon coating treatment during the preparation process, resulting in a portion of incompletely filled voids being exposed to the outside, thereby presenting a higher specific surface feature.
[0167] Table 2
[0168] project First charge capacity (mAh / g) First coulombic efficiency (%) 0.1C reversible capacity (mAh / g) 0.1C capacity retention rate (%) 1C reversible capacity (mAh / g) 1C capacity retention rate (%) 2C reversible capacity (mAh / g) 2C capacity retention rate (%) 3C reversible capacity (mAh / g) 3C capacity retention rate (%) 0.1C reversible capacity (mAh / g) 0.1C capacity retention rate (%) Example 1 1753.2 92.10 1560.3 89.00 1373.5 78.34 968.4 55.24 524.8 29.93 1573.5 89.75 Example 2 1698.2 90.60 1510.2 88.93 1305.6 76.88 867.4 51.08 532.0 31.33 1516.7 89.31 Example 3 1745.2 88.30 1552.7 88.97 1347.5 77.21 978.0 56.04 474.5 27.19 1561.6 89.48 Example 4 1762.4 81.60 1465.0 83.13 1199.3 68.05 809.5 45.93 378.6 21.48 1462.1 82.96 Example 5 1753.4 79.30 1450.9 82.75 1233.0 70.32 768.0 43.80 356.1 20.31 1446.7 82.51 Example 6 1631.6 83.70 1365.0 83.66 1088.9 66.74 534.0 32.73 224.2 13.74 1364.3 83.62 Example 7 1607.6 72.50 1350.5 84.01 1061.5 66.03 554.5 34.49 214.8 13.36 1347.0 83.79 Example 8 1751.2 86.40 1534.5 87.62 1286.8 73.48 859.5 49.08 469.7 26.82 1524.2 87.04 Example 9 1713.5 89.80 1495.7 87.29 1249.3 72.91 904.0 52.76 480.6 28.05 1488.2 86.85 Example 10 1730.5 91.30 1533.5 88.62 1312.7 75.86 910.7 52.63 481.2 27.81 1532.0 88.53 Comparative Example 1 1630.2 88.63 1470.6 82.95 1279.2 75.28 695.6 41.33 400.1 23.77 1462.7 86.90 Comparative Example 2 1519.2 82.31 1346.9 79.72 1108.3 67.22 606.0 37.85 255.1 15.93 1348.3 79.54 Comparative Example 3 1762.3 91.30 1531.8 86.92 1286.7 73.1 876.1 49.72 409.2 23.22 1505.7 85.44 Comparative Example 4 1960.4 87.5 1606.7 81.96 1320.1 67.34 901.7 46.00 247.2 12.61 1448.7 73.90
[0169] According to the electrochemical performance results in Table 2, the silicon-carbon composite materials obtained in Examples 1-10 have an initial charging capacity greater than 1600 mAh / g, and an initial efficiency substantially above 80% (79.3% in Example 5). The idea provided by the present invention can be used to prepare silicon-carbon negative electrode materials with excellent performance.
[0170] When silver trifluoromethanesulfonate is used for plating, the prepared material has relatively optimal electrochemical properties. Figure 3 As shown, the silicon-carbon composite material prepared in Example 1 has an initial charging capacity of 1753.2 mAh g -1 , the first coulombic efficiency reached 92.10%, showing excellent charge and discharge performance. Figure 4 When the rate performance test was performed, the silicon-carbon composite material prepared in Example 1 still maintained 524.8 mAh g at a current density of 3C. -1 reversible capacity.
[0171] It can be seen from Examples 1-10 that the type of metal compound gas, the radio frequency power of the equipment and the reaction temperature used during deposition have little effect on the material properties. When the metal source gas used is copper acetylacetonate and triethylaluminum, the prepared silicon-carbon composite material exhibits a relatively low reversible capacity and coulombic efficiency. Combined with the detection data in Table 1, it may be due to the short diffusion free path of copper plasma and aluminum plasma, and deposition mainly occurs on the surface of the material. Therefore, during the rate charge and discharge process, silicon is prone to shattering and falling off, and continues to react with the electrolyte, showing poor electrochemical behavior. In addition, when tin, germanium, and tungsten are plated, the material also exhibits relatively good performance.
[0172] Comparing the test data of Comparative Examples 1-3 with the examples, it can be seen that the composite of the metal coating and the silicon alloy particles helps to promote the stability of the overall structure of the negative electrode material. Comparative Examples 1-2 can be compared with Examples 1 and 4, and when the coating is missing, the prepared silicon-carbon composite material has a lower capacity released at a high rate, which further proves the superiority of the structure proposed by the present invention. Comparative Example 3 shows similar initial charge and discharge behavior to Examples 1-10, but shows a large gap at high current density. Comparative Example 3 shows lower reversible capacity and capacity retention than Examples 1-10 at a current density of 3C. This is because Comparative Example 3 lacks silicon alloy as an anchor point, which causes amorphous silicon to separate from the coating at high currents, resulting in loss of electrical performance.
[0173] By comparing the electrical performance data of Comparative Example 4 with that of Example 1, it can be obtained that when the silicon-carbon composite material is not subjected to carbon coating treatment, the first cycle efficiency of the material becomes low, and when tested at a high current density of 3C, the rate performance exhibits significantly deteriorated compared to Example 1. The presence of the carbon coating helps to isolate direct contact between silicon and the electrolyte, avoiding violent reactions during the charge and discharge process; in addition, the carbon coating also helps to improve the electrical conductivity of the material, thereby enabling rapid charge transfer at high current density.
[0174] Table 3
[0175] project 25℃, 100 cycles capacity retention rate (%) 0℃, 100 cycles capacity retention rate (%) 45℃, 100 cycles capacity retention rate (%) Example 1 85.31 73.85 76.71 Example 2 86.57 70.23 72.86 Example 3 83.05 69.88 73.44 Example 4 77.69 62.32 58.21 Example 5 70.42 57.94 60.08 Example 6 74.36 62.16 65.82 Example 7 60.82 53.41 51.27 Example 8 77.28 65.55 68.72 Example 9 77.80 63.06 65.28 Example 10 81.32 68.30 70.05 Comparative Example 1 82.96 61.58 65.34 Comparative Example 2 71.43 50.16 53.88 Comparative Example 3 72.24 59.43 63.92 Comparative Example 4 64.37 53.54 50.69
[0176] It can be seen from the above table that the silicon-carbon negative electrode materials prepared in Examples 1-10 exhibit more excellent reversible capacity and first coulombic efficiency, especially at high and low temperatures, the materials still exhibit excellent cycle stability.
[0177] Compared with Examples 1 and 4, Comparative Examples 1-2 show relatively low electrochemical performance at high and low temperatures. This is because the presence of the metal coating helps to stabilize the charge transfer between the active material and the lithium ions. Since the properties of the electrolyte are different at different temperatures, the viscosity increases at low temperatures, and the diffusion rate of lithium ions slows down, resulting in low capacity and efficiency; on the other hand, at high temperatures, since the diffusion rate of lithium ions becomes faster at this time, the intense charge transfer will cause greater stress in the active material, and the electrochemical performance will also be impaired. By constructing a coating-alloy particle composite structure, the de-lithiation and lithium insertion processes become more moderate. Therefore, at different temperatures, the material can exhibit relatively stable electrochemical properties.
[0178] By comparing the data of Comparative Example 3 with that of Example 1, it can be seen that the electrochemical performance of Comparative Example 3 is poor, and the electrochemical performance of the material will deteriorate significantly as the cycle proceeds. This is because the alloy particles attached to the coating can be used as anchor points, and the subsequent amorphous silicon deposition is mainly carried out on the anchor points. Therefore, the main active material of the material and the metal coating are closely connected. Compared with conventional silicon-carbon materials, this connection exists at the molecular level and can still be maintained at high current density, so the capacity of the material can be effectively released.
[0179] By comparing the data of Comparative Example 4 with that of Example 1, it can be seen that the electrochemical performance of Comparative Example 4 is poor, and the deterioration is more obvious when continuous charging and discharging is performed at high and low temperatures. This is because the presence of the carbon layer helps to reduce the specific surface area of the material. An excessively large specific surface area will form an uneven SEI layer during the first charge and discharge process. This structure will cause continuous consumption of the electrolyte during subsequent charge and discharge processes. As the cycle proceeds, the exposed active substances will directly react with the electrolyte, resulting in a dramatic volume expansion (≥300%) in the process, and the electrochemical performance of the material will significantly deteriorate.
Claims
1. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material comprises: Porous carbon matrix; A metal coating, wherein the metal coating is located on the pore walls of the porous carbon matrix; Silicon alloy particles, wherein the silicon alloy particles are located on the surface of the metal coating; Amorphous silicon particles, the amorphous silicon particles epitaxially growing along the silicon alloy particles; and A carbon coating layer is located on the outer layer.
2. The silicon-carbon composite material according to claim 1, characterized in that: The silicon-carbon composite material satisfies one or more of the following conditions a-f: a. D of the silicon-carbon composite material 10 2-6μm; b. D of the silicon-carbon composite material 50 6-11μm; c. D of the silicon-carbon composite material 90 11-30μm; d. The particle size distribution span of the silicon-carbon composite material 1.05-1.75; e. The silicon loading of the silicon-carbon composite material is 30%-70%, where the percentage is the mass of silicon in the silicon-carbon composite material as a percentage of the total mass of the silicon-carbon composite material; f. The BET specific surface area of the silicon-carbon composite material is 2-7 m 2 / g.
3. A method for preparing a silicon-carbon composite material, characterized in that: The preparation method comprises the following steps: S1, subjecting a porous carbon substrate to a first vapor deposition reaction using a first deposition gas to form a metal coating on the pore walls of the porous carbon substrate to obtain a first precursor; wherein the first deposition gas includes a first metal source gas; S2, subjecting the first precursor to a second vapor deposition reaction using a second deposition gas to form silicon alloy particles on the surface of the metal coating to obtain a second precursor; wherein the second deposition gas includes a second metal source gas and a second silicon source gas; S3, subjecting the second precursor to a third vapor deposition reaction using a third deposition gas, epitaxially growing amorphous silicon particles on the silicon alloy particles, to obtain a third precursor; wherein the third deposition gas comprises a third silicon source gas; S4, carbon-coating the third precursor to obtain a silicon-carbon composite material.
4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S1 satisfies one or more of the following conditions ae: a. The total flow rate of the first deposition gas is 400-800 sccm; b. The flow rate of the first metal source gas is 2-42 sccm c. The first metal source gas is a first metal compound gas; preferably, the first metal compound gas preferably includes one or more of Ag compound gas, Cu compound gas, Al compound gas, Sn compound gas, Ge compound gas and W compound gas; d. The first deposition gas further comprises a carrier gas and / or a reduction reaction gas; wherein, preferably, the flow rate of the carrier gas is 250-650 sccm; preferably, the flow rate of the reduction reaction gas is 20-200 sccm; e. The deposition pressure of the first vapor deposition reaction is 5-255 Pa; and / or, the RF power of the first vapor deposition reaction is 150-450 W; and / or, the deposition temperature of the first vapor deposition reaction is 300-800°C; and / or, the deposition time of the first vapor deposition reaction is 5-150 min.
5. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S2 satisfies one or more of the following conditions af: a. The total flow rate of the second deposition gas is 400-800 sccm; b. The flow rate of the second silicon source gas is 10-100 sccm; Preferably, the second silicon source gas is one or more of silane and silane halide, wherein the silane is preferably monosilane and / or dimethylsilane; c. The second deposition gas further comprises a carrier gas; wherein, preferably, the flow rate of the carrier gas is 250-650 sccm; d. The flow rate of the second metal source gas is 10-100 sccm; e. The second metal source gas is a second metal compound gas; preferably, the second metal compound gas preferably includes one or more of Ag compound gas, Cu compound gas, Al compound gas, Sn compound gas, Ge compound gas and W compound gas; f. The deposition pressure of the second vapor deposition reaction is 5-255 Pa; and / or, the deposition temperature of the second vapor deposition reaction is 300-800°C; and / or, the RF power of the second vapor deposition reaction is 150-450 W; and / or, the deposition time of the second vapor deposition reaction is 5-150 min.
6. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S3 satisfies one or more of the following conditions ae: a. The total flow rate of the third deposition gas is 400-800 sccm; b. The third deposition gas further comprises a carrier gas; Preferably, the flow rate of the carrier gas is 275-675 sccm; c. The flow rate of the third silicon source gas is 30-300 sccm; d. The third silicon source gas is one or more of monosilane, dimethylsilane and silane halide; e. The deposition temperature of the third vapor deposition reaction is 300-800° C.; and / or, the deposition time of the third vapor deposition reaction is 30-360 min.
7. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The carbon coating in step S4 is performed by a vapor deposition reaction using a fourth deposition gas, wherein the fourth deposition gas includes a carbon source gas and preferably satisfies one or more of the following conditions ae: a. The total flow rate of the fourth deposition gas is 400-800 sccm; b. The flow rate of the carbon source gas is 30-300 sccm; c. The carbon source gas comprises one or more of methane, ethylene and acetylene; d. The fourth deposition gas further comprises a dilution gas; wherein, preferably, the flow rate of the dilution gas is 275-675 sccm; e. The carbon coating temperature is 400-800°C; and / or the carbon coating time is 0.5-10 h.
8. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 3 to 7.
9. Use of the silicon-carbon composite material according to any one of claims 1, 2 and 8 as an electrode material in a battery.
10. A battery, characterized in that: The battery comprises the silicon-carbon composite material according to any one of claims 1, 2 and 8.
Citation Information
Patent Citations
Nano silicon-carbon composite material for secondary lithium battery as well as preparation method and application of nano silicon-carbon composite material
CN115020689A
Cited By
Preparation method of rolling-resistant and low-temperature-resistant silicon-carbon negative electrode material
CN120841516A
Preparation method of low-temperature-resistant and roll-pressing-resistant silicon-carbon negative electrode material
CN120841516B